2010
DOI: 10.3928/01477447-20100329-14
|View full text |Cite
|
Sign up to set email alerts
|

Implant Removal Following Surgical Stabilization of Patella Fracture

Abstract: Patella fractures are relatively common injuries. Tension band wiring is commonly used to treat displaced patella fractures. The goal of this study was to assess the outcome and implant removal rate following surgical stabilization of patella fracture. A consecutive series of 67 patients over a 6-year period was reviewed. Minimum follow-up to fracture healing (3 months) was available in 63 patients. Forty-three men and 24 women with a mean age of 49 years (range, 14-90 years) underwent surgical stabilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 28 publications
2
30
1
1
Order By: Relevance
“…The studies gave good functional outcomes, but the rate of implant removal was still on a higher side. [21] Gosal et al, performed a study comparing two groups for patella fracture fixation, one metallic group and the other a non-metallic group and concluded that the metallic group had higher infection and morbidity rates when compared to the non-metallic group and hence the study supported the use of non-metallic implants for patella fractures [22] . Limitations of the study that must be taken into account are this study is a single-center study with a relatively small sample of patients.…”
Section: Discussionmentioning
confidence: 94%
“…The studies gave good functional outcomes, but the rate of implant removal was still on a higher side. [21] Gosal et al, performed a study comparing two groups for patella fracture fixation, one metallic group and the other a non-metallic group and concluded that the metallic group had higher infection and morbidity rates when compared to the non-metallic group and hence the study supported the use of non-metallic implants for patella fractures [22] . Limitations of the study that must be taken into account are this study is a single-center study with a relatively small sample of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Further, single and multiple cannulated screws have been proposed for fixation of patellar fracture instead of tension-band wiring technique. Even good rates of success have been reported using pre-mentioning fixation technique, a high rate of second re-operation for implant removal has been detailed [2][3][4][5]. For this reason, different authors have advocated the use of non-metallic implant for fixation of patellar fractures such as bioabsorbable screws and non-absorbable sutures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…[19] Cerrahi olarak tedavi edilen patella kırıklarının yaklaşık %40'ında implant çıkarma amacıyla ikinci bir cerrahiye gereksinim vardır. [20] Cilt altındaki tellerin potansiyel tahrişi nedeniyle son yıllarda anteriyor gergi bandı tespitinde 5 numara örgülü polyester (Ethibond) dikiş veya biyobozunur materyal ile tespit gündeme gelmiştir. Yapılan iki çalışmada hem dikişin hem de biyobozunur materyallerin başarıyla kullanı-mı belirtilmiştir.…”
Section: Tedavi̇unclassified